Mineralogical and Geochemical Characterization of Jordanian Olivine and Its Ability to Capture CO2 by Mineralization Process - Dwairi, Reyad Al (Geological Agency, 2019)
DOI:10.17014/ijog.6.2.175-183Olivine rich rocks outcrop in Kharazeh area (KHO) and Jurf Eldaraweesh (JDO) Basaltic rocks southern Jordan. KHO and JDO have been characterized for their mineralogical and geochemical properties investigated for their potential use in CO2 capture by mineralization process. The effects of particle size, temperature, and contamination time were examined in the mineralization process. Two grain sizes of olivine for each type were used in capture experiments. The first grain size is the separated size fraction between 1 to 0.7 mm (KHO1 and JDO1), while the second grain size is the separated size fraction between 0.7 to 0.3 mm (KHO2 and JDO2). For the mineralization purpose, a chemical reactor was used to determine the olivine CO2 capture capacity. Thin section studies aided by XRD identification for KHO indicated the presence of olivine crystals as the main mineral with percentage reaches 48% plagioclase, augite, and magnetite. While the mineral content for JDO is (35%) olivine, plagioclase, clinopyroxene, and opaque minerals. Olivine chemical composition results show the high MgO percentage for KHO ranges between 47.5 and 50.13%, while the percentage of MgO varies from 43.6% and 44.6% for JDO. The CO2 mineralization process results were interpreted using percentage removal curves. CO2 capture percentage reaches the highest percentage (48%) using KHO2 and 100o C temperature. In summary, it can be concluded that CO2 can be removed from atmosphere using Jordanian olivine rich rocks.